Nutrition and yield of macadamia nut as affected by nitrogen doses - Perdoná, Marcos José; Martins, Adriana Novais; Suguino, Eduardo; Soratto, Rogério Peres (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the influence of nitrogen doses on mineral nutrition and yield of macadamia nut (Macadamia integrifolia). The experiment was carried out during three agricultural years, in Jaboticabal, SP, Brazil. The experimental design was a complete block with four replicates. Five doses of N (0, 50, 100, 150, and 200 kg ha-1 per year), applied as urea, were evaluated. The increase in N doses increased the nutrient concentration in the leaves and the yield of nuts and almonds. Ca, Mg, and S contents decreased and the ones of Fe and Mg increased linearly with N fertilization. Nut and almond yields were positively correlated with leaf N concentration, and the range from 14 to 18 g kg-1 allowed the highest yields. The dose of 150 kg ha-1 of N per year provides higher nut yields, without reducing the recovery rate of almonds.